Analisis Ketersediaan Sarana Prasarana Penyuluhan dan Kinerja Penyuluh Pertanian Lapangan di BP3K Kecamatan Unaaha Kabupaten Konawe - Irfan, Syaiful; Buana, Tjandra; Mardin, Mardin (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This study aims to find out the availability of Tools and Infrastructure facilities in BP3K Unaaha Subdistrict Konawe Regency, to know the performance of Agricultural Extension Workers in BP3K Unaaha Subdistrict Konawe Regency, and to know the relation of the availability of Tools and Infrastructure facilities With the performance of agricultural field extension workers in BP3K Unaaha Subdistrict of Konawe Regency. The research variables are extension Tools and Infrastructure (demonstration plots, equipment, and accessories for demonstration, transportation facilities, and availability of agricultural experiment results in the office) and performance of extension workers (working visit, work program, activity reporting, discipline). This research was conducted in Unaaha Subdistrict of Konawe Regency from February to April 2017. Respondents in this study were 8 people taken by the census, Data analysis of the availability of Tools and Infrastructure facilities and extension performance of field farmers using percentage, while to know the relationship of the availability of Tools and Infrastructure facilities extension And field agriculture extension performance used Rank Rank Correlation analysis or Spearman Rank Correlation. The result of the research shows that the availability of Tools and Infrastructure facilities was very available and the performance of agricultural field extension in Unaaha District was classified as a high category. The performance includes frequent working visits to the target area, always creating work programs, and always making monthly activity reports. Transportation variables have a significant relationship with the performance of agricultural field extension, demonstration plot, props, tool variables, and research results have a non-significant relationship with the performance of agricultural field extension workers in BP3K Kecamatan Unaaha Konawe District.